The specifics of technical and tactical training of elite level wrestlers - Latyshev S.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study – is to identify the specific features of the technical and tactical readiness of elite-level wrestlers. For this purpose, an analysis of the universal principles that guide these athletes during competitive fights was carried out. Methods and structure of the study. Within the framework of the research, an integrated approach was applied, including the study of specialized literature, pedagogical observation of the training and competitive process, video analysis of duels and systematization of best practices in the field of sports practice. Results and conclusions. The competitive activity of freestyle wrestlers at the Olympic Games was studied, starting with the 1996 Atlanta Olympics and ending with the 2024 Paris Games. The information from scientific publications, the results of pedagogical observations and the experience of leading experts are summarized. This made it possible to establish general trends in the conduct of a duel and, consequently, to determine the characteristic features of the technical and tactical preparedness of wrestlers of the highest athletic skill.